Supper with love : vibrant, delicious, and comforting plant-forward and pescatarian recipes for every day - Braxton, Michelle (Harvest, an imprint of William Morrow : HarperCollins Publishers, 2024)
"Beloved Southern Instagrammer and food blogger Michelle Braxton's long awaited debut cookbook is filled with delectable comfort food recipes that are plant-forward and pescatarian, easy-to-prepare and flexible, made with wholesome and seasonal ingredients, all shared in her signature warm and welcoming style." --